Evaluator Bias in Performance Evaluation of Online Transportation Driver: Empirical Study in Indonesia - Lufi Yuwana Mursita (The Indonesian Journal of Accounting Research, 2020)
Online transportation as a developing industry in Indonesia applies bonus-or-terminate incentives based on both objective and subjective performance evaluation. Regarding bias problems often found in the subjective evaluation, this paper aims to examine factors that influence bias in performance evaluation of the online transportation drivers. The data were collected by an online survey to users of online transportation in Indonesia using convenience sampling. Multiple regression analysis was utilized to analyze 163 data. The result shows that users of online transportation services tend to generate a biased rating, which is leniency bias. Altruism and knowledge of incentives scheme as the users’ internal factors significantly affect the biased evaluation. On the other hand, the external factors of the users, i.e., the frequency of usage and evaluation timing, do not significantly affect the biased evaluation. However, the other external factor, i.e., travel distance and duration, is found to affect the leniency bias positively. This paper concludes that more information related to the evaluation object and the inherent characteristic of an individual as the effect of collectivist national culture may lead to the generation of biased performance evaluation by the evaluator to help evaluated party avoiding penalty/termination in this competitive working environment.